2011
DOI: 10.1124/dmd.110.036830
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolism of Cinobufagin in Liver Microsomes from Mouse, Rat, Dog, Minipig, Monkey, and Human

Abstract: ABSTRACT:Cinobufagin (CB), a major bioactive component of the traditional Chinese medicine Chansu, has been reported to have potent antitumor activity. In this study, in vitro metabolism of CB among species was compared with respect to metabolic profiles, enzymes involved, and catalytic efficiency by using liver microsomes from human (HLM), mouse (MLM), rat (RLM), dog (DLM), minipig (PLM), and monkey (CyLM). Significant species differences in CB metabolism were revealed. In particular, species-specific deacety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…2). These findings agree well with our previous metabolic investigation of cinobufagin, which is a structural analog of RB (Ma et al, 2007;Ning et al, 2010;Ma et al, 2011). The significant differences in metabolic behaviors between rat and human suggested that rat could not serve as a preferred surrogate model for in vivo study of RB, and the in vivo pharmacological or toxicological data obtained in rat models previously may be misleading.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…2). These findings agree well with our previous metabolic investigation of cinobufagin, which is a structural analog of RB (Ma et al, 2007;Ning et al, 2010;Ma et al, 2011). The significant differences in metabolic behaviors between rat and human suggested that rat could not serve as a preferred surrogate model for in vivo study of RB, and the in vivo pharmacological or toxicological data obtained in rat models previously may be misleading.…”
Section: Discussionsupporting
confidence: 81%
“…By monitoring the apoptosis-associated protein, this investigation indicated that the anticancer bioactivities of 5-HRB were partially mediated through the activation of cytochrome c/caspase-dependent apoptotic signaling pathways for A549 cells. However, attention should be paid to the discrepancy between the present findings and the reported structurecytotoxic activity relationship of bufadienolides, which demonstrated that 5-hydroxylation reduced anticancer activity significantly (Kamano et al, 1998;Ma et al, 2011). The discrepancy makes apparent that the metabolic effect on bufadienolides may change case by case, making it meaningful to investigate the biotransformation of bufadienolides, which have great potential as a chemotherapeutic agents in oncology.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A number of reports have demonstrated that drugmetabolizing enzymes display significant species difference with regards to isoforms composition, expression and catalytic activities of drug-metabolizing enzymes [121][122][123]. CYP3A, the most important CYP isoform involved in the metabolism of xenobiotics, shows different substrate specificities in different species, resulting in inaccurate extrapolation from animal to human.…”
Section: Species Differences In Drug-metabolizing Enzymesmentioning
confidence: 99%
“…Miniature pig has been reported to possess similar kinetic parameters in the liver microsomes to human [9]. Thus it would be a better choice to serve as a surrogate model for drug metabolism.…”
Section: Introductionmentioning
confidence: 99%